2008
DOI: 10.1016/j.ajo.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless Amniotic Membrane Transplantation for Partial Limbal Stem Cell Deficiency

Abstract: PURPOSE-To evaluate the results of sutureless amniotic membrane (AM) transplantation using fibrin glue for reconstructing corneal surfaces with partial limbal stem cell deficiency (LSCD). DESIGN-Retrospective noncomparative interventional case series.METHODS-Eleven eyes of nine patients that had LSCD with 120 degrees to almost 360 degrees of limbal involvement underwent superficial keratectomy to remove the conjunctivalized pannus followed by AM transplantation using fibrin glue. Additional sutureless AM patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 36 publications
(48 reference statements)
1
78
0
Order By: Relevance
“…Kheirkhah and coinvestigators utilized fibrin glue-assisted AMT in patients with partial limbal cell deficiency and conjunctivochalasis. They were able to circumvent limbal epithelial stem cell transplantation, demonstrating the efficacy of fibrin glue-assisted AMT in successfully inducing corneal epithelial growth, leading to complete coverage of the AM [88]. In the conjunctivochalasis study, they reported effective attachment of the AM to bare sclera and development of a smooth conjunctival surface [89].…”
Section: Amtmentioning
confidence: 90%
“…Kheirkhah and coinvestigators utilized fibrin glue-assisted AMT in patients with partial limbal cell deficiency and conjunctivochalasis. They were able to circumvent limbal epithelial stem cell transplantation, demonstrating the efficacy of fibrin glue-assisted AMT in successfully inducing corneal epithelial growth, leading to complete coverage of the AM [88]. In the conjunctivochalasis study, they reported effective attachment of the AM to bare sclera and development of a smooth conjunctival surface [89].…”
Section: Amtmentioning
confidence: 90%
“…Although fibrin glue has been used for sealing amnion to the ocular surface 26,27 and is used for lowtension applications, clinical experience indicates that it has insufficient bonding strength required for large lacerations and stellate lacerations. The results of this study using a V-shaped incision mimicking a large irregular laceration support this experience.…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic membrane transplantation has been used successfully in conjunctival surface reconstruction due to its anti-inflammatory property and minimal scar formation [7,12,13]. Fibrin tissue adhesive has been widely applied in various medical fields, including ophthalmic surgery such as vitreoretinal, glaucoma, ocular surface, cataract and refractive surgery [3,4,5,6,7,8,9,13,14,15,16,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…When wide excisions are necessary for tumor surgery, autologous graft or labial mucosa can be used for surface reconstruction [1]. An alternative is the use of amniotic membrane graft, which has been used in ocular surface reconstruction in surgical scarring diseases of the cornea and conjunctiva [2,3,4,5,6,7,8]. The amniotic membrane is the innermost layer of the placenta and is a thick basal membrane with an avascular stroma [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation